A Retrospective Comparative Cohort Study Comparing Temporary Internal Fixation to External Fixation at the First Stage Debridement in the Treatment of Type IIIB Open Diaphyseal Tibial Fractures. Issue 3 (March 2019) - Fowler, Timothy; Whitehouse, Michael; Riddick, Andrew; Khan, Umraz; Kelly, Michael
Abstract : Objectives: To compare the rates of deep infection, flap failure, and nonunion after temporary internal fixation (TIF) with temporary external fixation (ex-fix) in the management of Gustilo–Anderson type IIIB open tibia fractures. Design: Retrospective comparative cohort study. Setting: Level 1 trauma center. Patients/Participants: Sixty-four consecutive patients with a Gustilo–Anderson type IIIB open diaphyseal tibia fracture (OTA/AO 42) were treated between May 2014 and May 2016. Forty-seven patients (TIF = 24; ex-fix = 23) met the inclusion criteria and underwent 2-stage reconstruction. Definitive fixation was with an intramedullary nail. Intervention: Temporary fracture stabilization at the first-stage debridement was achieved with either TIF with a plate or ex-fix. Main Outcome Measurement: The main outcome measure was deep infection. Results: There were 4 complications in the ex-fix group (3 infection and 1 nonunion) and 2 complications in the TIF group (1 infection and 1 flap failure). Multiple regression modeling revealed that infection ( P = 0.610), nonunion ( P = 0.918), and flap failure ( P = 0.112) were not significantly associated with the mode of temporary fixation or other demographic and treatment variables. The odds ratio of patients treated with TIF developing an infection compared with those treated with an ex-fix was 0.29 (95% confidence interval, 0.03–3.01). Conclusions: TIF of type IIIB open diaphyseal tibial fractures seems to be a safe alternative to conventional external fixation. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.